2021
DOI: 10.1002/ejic.202100816
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Site and Cooperative Bond Activation Reactions with Ylide‐Functionalized Tetrylenes: A Computational Study

Abstract: Due to their transition metal‐like behavior divalent group 14 compounds bear huge potential for their application in bond activation reactions and catalysis. Here we report on detailed computational studies on the use of ylide‐substituted tetrylenes in the activation of dihydrogen and phenol. A series of acyclic and cyclic ylidyltetrylenes featuring various α‐substituents with different σ‐ and π‐donating capabilities have been investigated which demonstrate that particularly π‐accepting boryl groups lead to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…To test this hypothesis, we initially performed density functional theory (DFT) calculations (PW6B95-D3/def2tzvp) on a series of germylenes with different ylide groups to study the impact of the Z substituent on the energy of the molecular orbitals, in particular on the germanium-centered orbitals representing the lone-pair and empty p-orbital (Figure 2, see the Supporting Information for details). [14] Compared to our recently reported sulfonyl-functionalized germylene Da the introduction of a pyridyl or phenyl group leads to an increased HOMO energy and no significant decrease of the LUMO energies, indicating that these germylenes would be even stronger nucleophiles. In contrast, the pentafluorophenyl and especially the cyano-substituted germylene featured lower energies for the orbitals representing the lone pair at germanium and importantly considerably lower LUMO energies, suggesting that they should exhibit a pronounced electrophilic character.…”
Section: Computational Studiesmentioning
confidence: 64%
See 2 more Smart Citations
“…To test this hypothesis, we initially performed density functional theory (DFT) calculations (PW6B95-D3/def2tzvp) on a series of germylenes with different ylide groups to study the impact of the Z substituent on the energy of the molecular orbitals, in particular on the germanium-centered orbitals representing the lone-pair and empty p-orbital (Figure 2, see the Supporting Information for details). [14] Compared to our recently reported sulfonyl-functionalized germylene Da the introduction of a pyridyl or phenyl group leads to an increased HOMO energy and no significant decrease of the LUMO energies, indicating that these germylenes would be even stronger nucleophiles. In contrast, the pentafluorophenyl and especially the cyano-substituted germylene featured lower energies for the orbitals representing the lone pair at germanium and importantly considerably lower LUMO energies, suggesting that they should exhibit a pronounced electrophilic character.…”
Section: Computational Studiesmentioning
confidence: 64%
“…In the solid‐state, 2 forms a C i symmetrical dimer, in which the two germyl anions are connected via the potassium ions thus forming a K 2 N 2 four‐membered ring as central structural motif (Figure 3). The germanium center is pyramidalized with acute C−Ge−C angles between 94.9(1) and 97.5(1)°, but features no contact to the metal ions, with the shortest Ge⋅⋅⋅K separation being longer than 4.5 Å [14] . The average Ge−C bond length amounts to approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the extensive range of carbenes (and their heavier analogues) that are known experimentally in terms of both structure and reactivity, ,,, the number and variety of stable group 13 carbenoids are very limited, and this calls for an in-depth study toward the design and development of novel stable group 13 carbenoids and probing of their potential in stabilizing unusual species as well as in reactions such as small-molecule activation. In this context, it is pertinent to mention the role of ylidic groups in enhancing the singlet state stability and nucleophilicity of divalent group 14 bases. Recently, we have computationally shown that ylidic groups could be used as building blocks for the stabilization of hitherto unknown boron­(I) carbenoids . Herein, we present the results of our computational studies toward stabilizing monovalent five-membered group 13 carbenoids (Scheme ; E = Al and Ga) by employing strongly electron-donating ylidic moieties.…”
Section: Introductionmentioning
confidence: 99%
“… 17 For example, bond activation reactions repeatedly proceeded via a bifunctional mechanism with active participation of the ylidic carbon center in the bond cleavage process. 18 Analogous studies with transition metals are yet unknown, but highly desirable for the development of novel catalytic transformations. Previous findings with the main group element compounds have shown that the stability of the metal-ylide bonding would benefit from further coordination sites that prevent elimination of the ylide from the metal sphere after the activation step.…”
Section: Introductionmentioning
confidence: 99%